2019
DOI: 10.34013/jk.v3i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Rasio Keuangan Untuk Menilai Kinerja Hotel Ciater Spa & Resort, Subang

Abstract: Financial ratio analysis of a company is one of financial performance assessment that are very useful to management in making plan for both short term and long term. The purpose of this research is to evaluate the implementation of financial statement analysis carried out by Hotel Ciater Spa & Resort in 2013 and 2014. The research method used is descriptive method. From the results of analysis show that the level of liquidity ratios, solvency, and operational is quite high, while the ratio of profitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A research in Ciater SPA & Resort Hotel, Subang, showed high level of liquidity (Saepudin, P. & Muslim, 2016). Besides that, ability of the company assets to guarantee debt increase and inventory turnover decrease and also the fluctuated earned profit margin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research in Ciater SPA & Resort Hotel, Subang, showed high level of liquidity (Saepudin, P. & Muslim, 2016). Besides that, ability of the company assets to guarantee debt increase and inventory turnover decrease and also the fluctuated earned profit margin.…”
Section: Introductionmentioning
confidence: 99%
“…Financial ratio is divided into some parts; they are liquidity ratio that refers to ability of the company to meet short term liabilities by using the easiest asset converted to cash, then activity ratioto measure the level of efficiency in the utilization of company resources, then the profitability ratio which provides an overview of the company's probability, and leverage ratio which describes the company's ability to fulfill all of its obligations (Syuhada et al, 2020). Other than that, operational ratio is used to help the management to analyze the operational department of the company especially in restaurants and hotels (Saepudin, P. & Muslim, 2016).…”
Section: Introductionmentioning
confidence: 99%